Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2017
DOI: 10.1503/cjs.017916
|View full text |Cite
|
Sign up to set email alerts
|

Analyzing the risk factors influencing surgical site infections: the site of environmental factors

Abstract: Background: Addressing surgical site infection (SSI) is accomplished, in part, through studies that attempt to clarify the nature of many essential factors in the control of SSI. We sought to examine the link between multiple risk factors, including environmental factors, and SSI for prevention management. Methods:We conducted a longitudinal prospective study to identify SSIs in all patients who underwent interventions in 2014 in 8 selected hospitals on the Mediterranean coast of Spain. Risk factors related to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
50
0
4

Year Published

2017
2017
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 57 publications
(57 citation statements)
references
References 40 publications
1
50
0
4
Order By: Relevance
“…Surgeons often irrigate the surgical site throughout a procedure with sterile saline to improve visibility, keep tissues moist, and remove contaminants, although this is not universally practiced. Despite the potential benefit of surgical irrigation, there is virtually no standardization of the practice across all surgical specialties, and no official guideline from any major professional or accrediting organization . The type of irrigation fluid, additives (eg, antiseptics, antibiotics), volume, and delivery method vary widely and are rarely reflected in departmental protocols or SSI prevention bundles …”
Section: A Bundle To Standardize the Incision Closure Processmentioning
confidence: 99%
“…Surgeons often irrigate the surgical site throughout a procedure with sterile saline to improve visibility, keep tissues moist, and remove contaminants, although this is not universally practiced. Despite the potential benefit of surgical irrigation, there is virtually no standardization of the practice across all surgical specialties, and no official guideline from any major professional or accrediting organization . The type of irrigation fluid, additives (eg, antiseptics, antibiotics), volume, and delivery method vary widely and are rarely reflected in departmental protocols or SSI prevention bundles …”
Section: A Bundle To Standardize the Incision Closure Processmentioning
confidence: 99%
“…The likelihood, severity, and type of an SSI can be dependent on intrinsic factors, such as the patient's age and underlying comorbidities and the type and length of the surgical procedure 4 . Extrinsic factors in the OR, such as health care provider (HCP) behavior and practices that modify air movement, the physical environment, equipment, or surgical instruments, also can increase microbial contamination and the risk of SSI development 5‐13 . Patients and HCPs can help control the effects of these intrinsic and extrinsic factors with practices such as cessation of smoking, preoperative bathing, preoperative prophylactic antibiotics, alcohol‐based patient skin antisepsis, and maintenance of body temperature 2,4 …”
Section: Airborne Sources and Control Of Contaminantsmentioning
confidence: 99%
“…In the OR environment, microbial contamination can occur through an airborne or contact route. The potential exists for microbes to infect the surgical incision through one of these routes, resulting in a reported association between OR contaminants and SSIs 5,6,8,11 . However, not every study has found a strong link between air or surface contamination and infection 7 .…”
Section: Airborne Sources and Control Of Contaminantsmentioning
confidence: 99%
See 2 more Smart Citations